Kardiovaskuläre Notfall- und Akutmedizin - Möckel, Martin; Radke, Peter W.; Wolfrum, Sebastian (De Gruyter, 2020)
Diagnostic and therapeutic interventions are developed based on the patient's initial emergency presentation. The textbook emphasizes criteria for monitoring, selecting inpatient versus outpatient care, diagnostic sequences, and determining the urgency of specific steps in the treatment process. Case vignettes provide practical guidance, along with diagnostic flowcharts and take-home messages.